2006
DOI: 10.1158/0008-5472.can-05-3907
|View full text |Cite
|
Sign up to set email alerts
|

Global Gene Expression Profiling of Pleural Mesotheliomas: Overexpression of Aurora Kinases and P16/CDKN2A Deletion as Prognostic Factors and Critical Evaluation of Microarray-Based Prognostic Prediction

Abstract: Most gene expression profiling studies of mesothelioma have been based on relatively small sample numbers, limiting their statistical power. We did Affymetrix U133A microarray analysis on 99 pleural mesotheliomas, in which multivariate analysis showed advanced-stage, sarcomatous histology and P16/CDKN2A homozygous deletion to be significant independent adverse prognostic factors. Comparison of the expression profiles of epithelioid versus sarcomatous mesotheliomas identified many genes significantly overexpres… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

27
188
1
4

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 232 publications
(220 citation statements)
references
References 52 publications
27
188
1
4
Order By: Relevance
“…40,41 Despite the differences between peritoneal and pleural mesotheliomas, previous studies have demonstrated homozygous CDKN2A deletions in malignant mesothelioma are a poor prognostic indicator regardless of site. 22,25,32 Consistent with these reports, we found that patients with peritoneal mesothelioma harboring a homozygous CDKN2A deletion had decreased PFS and OS. In addition, patients with a hemizygous NF2 loss also exhibited poor PFS and OS.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…40,41 Despite the differences between peritoneal and pleural mesotheliomas, previous studies have demonstrated homozygous CDKN2A deletions in malignant mesothelioma are a poor prognostic indicator regardless of site. 22,25,32 Consistent with these reports, we found that patients with peritoneal mesothelioma harboring a homozygous CDKN2A deletion had decreased PFS and OS. In addition, patients with a hemizygous NF2 loss also exhibited poor PFS and OS.…”
Section: Discussionsupporting
confidence: 90%
“…[21][22][23] In addition, homozygous CDKN2A deletions are a poor prognostic indicator for patients with pleural mesothelioma. 22,24,25 NF2, located on chromosome 22q12, is mutated in 50% of pleural mesotheliomas with corresponding loss of the wild-type allele by deletion of either 22q or all of chromosome 22. 16,26 Hemizygous loss of NF2 is associated with increased mesothelioma proliferation, invasiveness, spreading, and migration.…”
mentioning
confidence: 99%
“…These data are in contrast to those of M Ladanyi's laboratory (USA), who found that the accuracy of these microarrays is consistently lower than reported by Bueno and by others, and that their power in clinical prognostication has been overestimated (Lopez-Rios et al, 2006). JR Testa and colleagues (USA) exposed heterozygous Nf2 knockout mice to asbestos by intraperitoneal injection.…”
contrasting
confidence: 58%
“…24 One of the most common genetic alterations in mesothelioma is the homozygous deletion of the 9p21 locus within a cluster of genes that includes CDKN2A, CDKN2B and MTAP. [25][26][27][28] Several cytogenetic and molecular studies have reported p16/ CDKN2A deletions in up to 72% of primary mesotheliomas. 29,30 Thus, detection of homozygous p16/ CDKN2A deletion by fluorescence in situ hybridization (FISH) seems to be feasible and helpful in confirming a diagnosis of mesothelioma in cytologic and surgical specimens.…”
mentioning
confidence: 99%